Enterprise Integration Patterns Designing, Building, and Deploying Messaging Solutions - Hohpe, Gregor; Woolf, Bobby (Addison Wesley Professional, 2003)
Annotation
Keywords: Telecommunication -- Message processing; Telecommunication; Data Processing; Management Information Systems; Technology & Engineering; Telecommunications; Computers; Management Information Systems; Telecommunication